SURAT TANDA BUKTI HAK WARIS DALAM PENDAFTARAN HAK MILIK ATAS TANAH DI KECAMATAN SUKOHARJO KABUPATEN SUKOHARJO - Andria Luhur Prakoso (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The research, entitled “The Documents of Inheritance For Over Land Registration of Property Rights in Sukoharjo District of Sukoharjo Regency” aims to find out the implementation of regulatory and compliance proof of inheritance in the registration of property rights over land in Sukoharjo, Sukoharjo District, a great variety of problems and efforts being made to overcome these problems in the registration of qualified property rights over the land as inheritance in the form of letter proof of inheritance in Sukoharjo district of Sukoharjo Regency.This study is an empirical juridicial research, which concerns the effectiveness of the law, particularly with regard to the letter proof of inheritance. Data collection is carried out by means of field research to obtain primary data and libraries research to acquire secondary data. Research results are analyzed qualitatively by selecting, grouping, systemizing, and linking data with the norms and principles, thus the writer obtained a clear picture linked to the problems being observed. The result showed that the certificate is evidence of the inheritance functions as a legitimate instrument of proof in Sukoharjo Land Office is that the document of proof plate as an Heir or Beneficiary Certificate; and deed of Divisian Right Along (APHB), and refused the documents of inheritance in the form of deed of Division of Inheritance. Implementation of publishing documents of Inheritance in the form of affidavits heir in Sukoharjo District of Sukoharjo Regency under Article 111, paragraph (1) letter (c) of the figure (4) K.BPN/PMNA No.3 in 1997. Barriers compliance the documents of inheritance among others are from the society’s minimal awareness of the law, ignorance of the procedures and mechanisms of registration of land. Efforts are being made in anticipating and addressing the obstacles faced and effective remains unclear, both from the public and government authorities so that the principles and objectives of the appropriate land registration a Government Regulation No. 24 of 1997 about the land registration has not been fully achieved.Keywords: the documents of inheritance, registration of property rights over land.